2008
DOI: 10.1007/s11596-008-0205-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling on acute rejected transplant kidneys with microarray

Abstract: To investigate the gene expression profiles in acute allograft rejection of renal transplantation, and identify the markers for the early diagnosis of acute rejection, heterotopic kidney transplantation was performed by using F344 or Lewis donors and Lewis recipients. No immunosuppressant was used. Renal grafts were harvested on days 3, 7, and 14. A commercial microarray was used to measure gene expression levels in day-7 grafts. The expression levels of 48 genes were up-regulated in the allograft in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…If the fluorescence signal of the both pathways met the effective signal standard, at least 2-fold changes relative to the control were considered to be threshold. If effective hybridization signals were just in one of the pathways, 3-fold changes relative to the control was taken as threshold [8].…”
Section: Hybridization Signal Analysis and Standardizationmentioning
confidence: 99%
See 1 more Smart Citation
“…If the fluorescence signal of the both pathways met the effective signal standard, at least 2-fold changes relative to the control were considered to be threshold. If effective hybridization signals were just in one of the pathways, 3-fold changes relative to the control was taken as threshold [8].…”
Section: Hybridization Signal Analysis and Standardizationmentioning
confidence: 99%
“…The cDNA microarray utilizes the theory of gene chip technology of information integrating and processing in parallel, and mounts an enormous number of specific oligonucleotide or DNA fragment on a 645 square millimeter matrix, conducting high efficiency and low consumption in the process of assessing the biological information [7]. After investigating the gene expression profiles in acute allograft rejection of renal transplantation, it was found that the early diagnosis was virtually impossible to make based on a single gene marker, but could be achieved by a set of gene markers [8]. In this study, cDNA microarray technology was applied to differentiate the gene expression spectrum of GCTB, trying to explore the relationship between gene expression spectrum and the clinical presentation, and further provide evidences for gene diagnosis and potential gene therapy 2 Materials and methods…”
Section: Introductionmentioning
confidence: 99%